Health Action Process Approach (HAPA) as a Theoretical Framework to Understand Behavior Change - Schwarzer, Ralf (2016)
A theoretical framework to explain, predict, and modify health behaviors is presented which consists of various psychological constructs and a mediator mechanism. Risk perception, outcome expectancies, self-efficacy, intention, planning, and action control constitute the building blocks for a mediator model that is based on two processes: goal setting and goal pursuit. When it comes to the development of interventions to modify behaviors, one can target either the initial motivation phase or the subsequent volition phase. This is an open architecture framework allowing for various research designs and subsets of constructs. Hundreds of studies have been conducted based on this model. Three correlational and two intervention studies were chosen to illustrate the diversity of approaches targeting physical activity in Germany and Costa Rica, dental cleaning in India and Poland, and dust mask wearing in China. They differ in terms of the predictors that emerged as most relevant for behavior change.